Tools for teaching comprehensive human sexuality education : lessons, activities, and teaching strategies utilizing the national sexuality education standards - Splendorio, Dominick, 1949-; Reichel, Lori, 1966-
"Practicing health educators, students, and other professionals who work with teens and young adults will discover arich selection of activities and lessons. This authoritative guide is based on the most current version of the National Health Education Standards' new National Sexuality Education Standards, and Sex Information and Education Council of the United States guidelines. It provides educators with teacher-friendly interactive activities that engage students' thinking and decision making skills in and out of the classroom. The book covers a broad range of issues related to human sexuality"--